2006
DOI: 10.1016/j.neuron.2006.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Neural Signatures of Economic Preferences for Risk and Ambiguity

Abstract: People often prefer the known over the unknown, sometimes sacrificing potential rewards for the sake of surety. Overcoming impulsive preferences for certainty in order to exploit uncertain but potentially lucrative options may require specialized neural mechanisms. Here, we demonstrate by functional magnetic resonance imaging (fMRI) that individuals' preferences for risk (uncertainty with known probabilities) and ambiguity (uncertainty with unknown probabilities) predict brain activation associated with decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
502
8
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(578 citation statements)
references
References 48 publications
61
502
8
2
Order By: Relevance
“…Similar comparisons of the neural correlates of risk and ambiguity have been done by other groups 64,65 . An fMRI study found that subjects' preferences for ambiguity correlate with activation in lateral prefrontal cortex, whereas preferences for risk correlate with activity in parietal cortex 64 .…”
Section: Neuroeconomics Of Decision Making Under Uncertaintysupporting
confidence: 54%
“…Similar comparisons of the neural correlates of risk and ambiguity have been done by other groups 64,65 . An fMRI study found that subjects' preferences for ambiguity correlate with activation in lateral prefrontal cortex, whereas preferences for risk correlate with activity in parietal cortex 64 .…”
Section: Neuroeconomics Of Decision Making Under Uncertaintysupporting
confidence: 54%
“…Of the regions that responded to the cue, there was a range of relationships to probability, but in almost all cases the biological probability weighting function displayed an "inverted-S" shape, which is characteristic of the behavioral probability weighting function hypothesized in prospect theory. Regions that have been previously associated with probabilistic decision making, notably in the parietal cortex (Huettel et al, 2006;Platt and Glimcher, 1999;Shadlen and Newsome, 2001), showed significant forms of nonlinearity (Tables 1 & 2). Regions of the parietal cortex, specifically LIP in monkeys, have been proposed to contain a map of the expected utility of all possible actions (Glimcher et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…This facilitated the solution of economic models employing the assumption that economic actors made decisions with the purpose of attaining preferred outcomes. Neuroeconomists, in contrast, have recently advanced the hypothesis that utility is a neural response and that activations of certain brain regions provide measures of utility, in the sense that individuals make decisions as if they are maximizing the activation of these regions Glimcher, 2002;Hsu et al, 2005;Huettel et al, 2006;Knutson et al, 2005;Preuschoff et al, 2006). We take a similar approach here.…”
Section: Introductionmentioning
confidence: 99%
“…Regions that have been previously associated with probabilistic decisionmaking, notably in the parietal cortex (Huettel et al, 2006;Platt & Glimcher, 1999;Shadlen & Newsome, 2001;Glimcher, Dorris, & Bayer, 2005), showed significant forms of nonlinearity. We found maps for both probability and magnitude adjacent to each other near the temporo-parietal junction.…”
Section: Probability Weightingmentioning
confidence: 90%
“…Preparation for a withdrawal response has been linked to activity in mid-ACC and supplementary motor area (SMA). We take measures of activation of these regions as a measure of disutility, in an analogous manner to authors who have interpreted activation of other regions as a measure of positive utility (Camerer et al, 2005;Glimcher, 2002;Hsu, Bhatt, Adolphs, Tranel, & Camerer, 2005;Huettel, Stowe, Gordon, Warner, & Platt, 2006;Knutson, Taylor, Kaufman, Peterson, & Glover, 2005;Preuschoff, Bossaerts, & Quartz, 2006).…”
Section: Why Do People Want To Get An Adverse Experience Over With Asmentioning
confidence: 99%